Preparation of homogeneous hydrogels by controlling the crosslinker reactivity and availability - ABDURRAHMANOĞLU, SUZAN (TAYLOR & FRANCIS INC, 2008)
Network microstructures of polyacrylamide (PAAm) hydrogels were investigated by static light scattering measurements. The gels were prepared by free-radical crosslinking polymerization of acrylamide (AAm). To suppress the degree of gel inhomogeneity, the crosslinker reactivity during gelation was controlled by decreasing its availability in the reaction system. Our first approach was the addition of the crosslinker N,N'-methylenebis(acrylamide) (BAAm) in one or three portions during the course of the gelation reactions. As a second approach, a slightly water soluble crosslinker, namely ethylene glycol dimethacrylate (EGDM) was used as a crosslinker in AAm polymerization. Due to the low water solubility of EGDM, EGDM phase in the gelation system act as a reservoir of crosslinker so that the crosslinker can be supplied continuously to the aqueous reaction zone during the course of gelation. It was found that the delayed crosslinker addition technique further increases the degree of inhomogeneity of PAAm hydrogels. The results were explained with increasing viscosity of the reaction solution at the time of the crosslinker addition so that the crosslinking reactions are limited to local regions in the reaction system. The second approach, namely use of the slightly water soluble crosslinker EGDM significantly increases the degree of structural homogeneity of PAAm hydrogels.
Keywords: homogeneous hydrogels; inhomogeneity; light scattering; gelation; ANGLE NEUTRON-SCATTERING; SPATIAL INHOMOGENEITY; POLYACRYLAMIDE HYDROGELS; LINKING COPOLYMERIZATION; POLYMER GELS; TEMPERATURE